Prevention Effort of Leprosy Reactions Based on Risk Factor Analysis at Sumberglagah Leprosy Hospital Mojokerto - Ramadhona, A; Supriyanto, S; Martini, S (KnE Life Sciences, 2018)
The background of this study is the increasing number of leprosy reaction incidence treated at Sumberglagah Leprosy Hospital from 6.76% to 10.3% in September 2016. The purpose of this study is to generate recommendations for leprosy reaction prevention efforts based on risk factor analysis at Sumberglagah Leprosy Hospital of Mojokerto. The method of research was an observational analytic study with crosssectional design. The sampling technique applied in this study was total sampling, meaning that all the sample cases became respondent consisting of patients coming to Sumberglagah Leprosy Hospital Mojokerto from February 13, 2017 to April 12, 2017, not new patients, not yet released from control, and willing to became respondent. Based on these criteria, we got 43 respondents. Data collection techniques applied in this study were interviews with questionnaires, medical record review, and focal group discussions. The results show four variables of individual factors that influence the incidence of leprosy reaction, namely, leprosy type (p = 0.022 and beta = –0.997), comorbid infections (p = 0.023 and beta = 0.319), physical stress (p = 0.001 and beta = –0.431), and behavioral stress (p = 0.016 and beta = 0.393). The environmental factor influencing the incidence of leprosy reaction constitutes one variable of selfstigma (p = 0.025 and beta = –0.226). While for health service factor, there are two variables that influenced the incidence of leprosy reaction, that is, compliance in treatment of MDT (multidrug therapy) (p = 0.021 and beta = –0.349) and counseling by officer (p = 0.011 and beta = –0.247). Recommendations of preventions effort of leprosy reactions based on risk factor analysis can be carried out through primary prevention efforts (health promotion and counseling) and secondary prevention efforts (early diagnosis and prompt treatment and disability limitation). The tertiary prevention effort (rehabilitation) may include group therapy and occupational therapy. Keywords: prevention effort, leprosy reaction, risk factor, leprosy hospital